The Identifikasi Sub Faktor Manusia dalam Pertimbangan Desain Angkutan Barang Menggunakan Sepeda Motor Penumpang - Izzatul Jannah; Wildan Aulia (Aliansi Desainer Produk Industri Indonesia (ADPII), 2022)
ABSTRACT In the present day, the courier is getting more intense. Motorcycles are the couriers' preference because they are fast and flexible for various types of roads and traffic conditions. However, the use of passenger motorcycles as courier vehicles is not appropriate. This inappropriateness raises problems related to the human factor. This study aims to determine the sub-factor of the human factor in the issue of couriers who use motorcycles by ignoring the function of motorcycles as passenger vehicles. Research board analysis is used to analyze data collected from notes, photos, and videos of exploration by conditioning the researcher as a courier (exploring by doing method). The results showed that the dominant sub-factors identified were control, postural, work station, tool utility, and psychology. However, habituation and adaptation can increase tolerance for error. This study provides an argument that in determining the design aspects, preliminary studies related to relevant factors are important to do. Keywords: human factor, courier, motorbike